Atopic dermatitis in premature and term children. Issue 3 (1st October 2008) - Kvenshagen, B; Jacobsen, M; Halvorsen, R
Abstract : Objective: To investigate the prevalence of atopic dermatitis (AD) in premature compared with term children, the frequency of food allergy in children with AD, and the possible differences in prevalence of AD in children delivered by caesarean section compared with vaginally delivered children. Design: Prospective follow-up study over 2 years. Method: 609 children (193 premature and 416 term) were included. At 2 years, 512 children (161 premature and 351 term) participated. Children with symptoms consistent with AD/possible food allergy were examined, and the dermatitis was evaluated according to the SCORAD index. Skin prick test, specific IgE, elimination/challenge and DBPC challenge were performed. Results: 18.6% (95/512) of the children (19.9% (32/161) premature and 17.9% (63/351) term) had a diagnosis of AD. The prevalence of adverse reactions to food in all the children with AD was 15.8% (15/95) (similar in preterm and term children). AD was found in 17.5% (30/171) of children delivered by caesarean section, and 19.1% (65/341) delivered vaginally Conclusions: The prevalence of AD in the first 2 years of life was 18.6%, with no significant difference between preterm and term children. Adverse reactions to food were found in 15.8% (a similar prevalence in premature and term children). Mode of delivery did not affect prevalence of AD.